Phosphorus-doped PGM-type catalysts and catalytic systems for storage and release of hydrogen from organic hydrogen supports
By depositing phosphorus-doped PGM metal particles on solid support materials, using phosphorus-doped platinum group metal catalysts, the problem of low hydrogen storage and release efficiency in the prior art is solved, and the conditions of lower temperature and pressure are achieved efficient hydrogenation and dehydrogenation reaction.
Patent Information
- Application Number
- CN202380048172.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-26
- Filing Date
- 2023-10-26
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has problems of low efficiency and high energy consumption in hydrogen storage and release, especially in low temperature and high pressure conditions, making it difficult to achieve efficient hydrogenation and dehydrogenation reactions.
Using phosphorus-doped platinum group metal (PGM) type catalyst, the catalytic activity is improved by depositing phosphorus-doped PGM metal particles on solid support materials, thereby achieving efficient hydrogenation and dehydrogenation reactions under lower temperature and pressure conditions.
The rate of hydrogenation and dehydrogenation reaction of organic hydrogen carrier molecules is significantly improved, and the degree of efficient dehydrogenation can be achieved in a short period of time, reducing energy consumption, and improving the efficiency of hydrogen storage and release.
Smart Images

Figure BDA0005196789350000021 
Figure BDA0005196789350000041 
Figure BDA0005196789350000051
Abstract
Description
[0001] describe
[0002] The present invention relates to catalysts useful for hydrogenating and dehydrogenating organic hydrogen carrier compounds and their production. These catalysts consist of special phosphorus-doped PGM-type catalysts. They can be used to store and release hydrogen as required, for example in fuel cells for electric propulsion vehicles. Likewise, a device comprising the catalyst of the invention and its use is envisaged.
[0003] In the EU's "Green Deal" concept, the decarbonization of mobility is a main pillar. Several aspects of this have been proposed and discussed intensively in the field (https: / / europa.eu / newsroom / content / presentation-efficient-and-green-mobility-package_en). When it comes to carbon-free propulsion of vehicles, hydrogen fuel is often mentioned as a promising energy carrier, especially if the hydrogen is produced from sustainable resources such as wind or solar energy.
[0004] Hydrogen exists in the first period of the periodic table, in group 1, i.e. it is the lightest element. Hydrogen rarely exists in pure form in the atmosphere. In a flame of pure hydrogen burning in air, hydrogen (H 2 ) and oxygen (O 2 ) to form water (H 2 O) and releases energy.
[0005] 2H 2 (g)+O 2 (g) → 2H 2 O(g)+energy
[0006] The combustion of hydrogen in atmospheric air, rather than pure oxygen, produces small amounts of nitrogen oxides and water vapor.
[0007] The heat of combustion of hydrogen gas is about three times greater on a weight basis than hydrocarbon-based fuels, making it an efficient and attractive energy carrier. However, due to the very low density of hydrogen gas, the energy density on a volume basis is low compared to hydrocarbon fuels.
[0008] Hydrogen fuel is a zero carbon fuel when burned with oxygen. It can be used in fuel cells or internal combustion engines (eg HICEV). Regarding hydrogen-propelled vehicles, hydrogen has begun to be used in commercial fuel cell vehicles (such as buses) and has been used in fuel cell buses for many years.
[0009] Fuel cells, in particular proton exchange membrane fuel cells (PEMFC), also known as polymer electrolyte membrane (PEM) fuel cells, are primarily developed for transportation applications. Their distinguishing features include a lower temperature / pressure range (50°C to 100°C) and a special proton-conducting polymer electrolyte membrane ( https: / / en.wikipedia.org / w / index.php?title =Proton-exchange_membrane_fuel_cell&oldid=1064212583 ). Proton exchange membrane fuel cells convert the chemical energy released during the electrochemical reaction of hydrogen and oxygen into electrical energy, which is opposite to the direct combustion of hydrogen gas and oxygen gas to produce heat energy. The hydrogen gas stream is delivered to the anode side of the membrane electrode assembly (MEA). At the anode side, it is catalytically split into protons and electrons. The oxidation half-cell reaction or hydrogen oxidation reaction (HOR) is represented by the following:
[0010] H 2 →2H + +2e -
[0011] The newly formed protons permeate through the polymer electrolyte membrane (PEM) to the cathode side. The electrons travel along the external load circuit to the cathode side of the MEA, thereby generating the current output of the fuel cell. At the same time, a stream of oxygen is delivered to the cathode side of the MEA. At the cathode side, the oxygen molecules react with the protons that permeate through the polymer electrolyte membrane and the electrons that arrive through the external circuit to form water molecules. This reduction half-cell reaction or oxygen reduction reaction (ORR) is represented by the following:
[0012]
[0013] In order to provide hydrogen to fuel cells, for example in mobile applications, the storage of hydrogen for the intended use is one of the main technological challenges for the future. Methods for storing hydrogen include mechanical methods, such as high pressure and low temperature, or releasing H when needed. 2 Interest in using hydrogen as on-board energy storage in zero-emission vehicles is driving the development of new storage methods that are better suited for this new application. The first challenge is that hydrogen has a very low boiling point: it boils at about -253°C. Reaching such low temperatures requires a lot of energy.
[0014] To date, there are several methods that allow hydrogen to be stored. Compressed or liquefied hydrogen is a form of storage in which hydrogen gas is kept under pressure to increase storage density. Compressed hydrogen in hydrogen tanks at 350 bar (5,000 psi) and 700 bar (10,000 psi) is used for hydrogen tank systems in vehicles. Another form of storing hydrogen is to chemically bind it to a carrier. Metal hydrides, ammonia and liquid organic carriers, among others, are hotly discussed as promising solutions, especially for mobile hydrogen storage applications.
[0015] Liquid organic compounds that can be used to store hydrogen are called liquid organic hydrogen carriers (LOHCs). These are unsaturated organic compounds that can store useful amounts of hydrogen and release the stored hydrogen on demand. These LOHCs are hydrogenated for storage and dehydrogenated again when hydrogen is needed, for example, in a fuel cell. Using LOHCs, relatively high gravimetric storage densities (about 7 wt. % H per LOHC) can be achieved. 2 ), with a bulk density of 700 bar H 2 about twice that of liquid H 2 quite.
[0016] The function of the LOHC is described as follows. The low energy form of the LOHC is reversibly converted to an energy-rich form by hydrogenation with hydrogen, which in the reverse reaction recovers hydrogen from the hydrogenation product and forms the low energy form simply by increasing the temperature and / or reducing the hydrogen pressure. Therefore, the reaction is reversible. Reversible means that the material is converted from a low energy dehydrogenated state to an energy-rich hydrogenated state and then back to a low energy dehydrogenated state without significant loss of LOHC material. In the best case, these reversible steps can be repeated indefinitely. The reaction can be carried out in a flow reactor, a packed bed reactor, a stirred reactor to produce hydrogen and dehydrate LOHC, or in a batch reactor. In a batch reactor, the hydrogenation and dehydrogenation steps can be carried out at the same LOHC loading without the need to reload the LOHC after dehydrogenation.
[0017] In practice, both hydrogenation and dehydrogenation reactions require a catalyst. The hydrogenation and dehydrogenation reactions can be carried out at different locations and in this way, the LOHC material provides a method for transporting energy in the form of hydrogen over longer distances without any loss or consumption of hydrogen or LOHC material. In particular, the advantageously available LOHC allows such a reversible conversion under technically relevant conditions (pressure and temperature are mentioned as examples).
[0018] Several patents and patent applications have taught the use of LOHC in fuel cell applications (WO2020120261A1, WO2020064222A1, WO2018228895A1, DE102017201451A1, US2016061383AA, DE102012004444A1). LOHC is considered to refer to a group of chemical substances, such as those described in Energy Environ. Sci., 2011, 4, 2767 or US20100081034AA or Huang et al., J. Am. Chem. Soc, 2009, 131 (39), pp. 13898-13899 and Fang et al., J Am. Chem. Soc, 2009, 131 (42), pp. 15330-15338 and https: / / en.wikipedia.org / w / index.php?title=Liquid_ organic_hydrogen_carri-ers&oldid=1071399187 or https: / / en.wikipedia.org / w / index.php? title=Hydro-gen_storage&oldid=1080342247 .
[0019] There are many known LOHC systems. LOHC systems are usually based on cyclic hydrocarbon molecules (Heublein, N. et al., International Journal of Hydrogen Energy 2020, 45(46), 24902-24916 https: / / doi.org / 10.1016 / j.ijhydene.2020.04.274 ; Kwak et al., Energy Conversion and Management, 2021, 239, 114124 https: / / doi.org / 10.1016 / j.enconman.2021.114124 ). Firstly, polycyclic aromatic hydrocarbons, such as dibenzyltoluene, benzyltoluene, which are used as industrial heat transfer fluids today, are mentioned. known or their isomeric mixtures (Scheme 1).
[0020]
[0021] Option 1: Special LOHC
[0022] The method and arrangement are intended to safely and technically simply supply pure hydrogen to various vehicles (such as, for example, motor vehicles, buses, trucks, forklifts, ships, trains, etc., collectively referred to as "vehicles"). Thus, there is the advantage of not having to re-equip filling stations for operation at very low temperatures or very high pressures, which is expensive (as in the case of liquid hydrogen), but continuing to use the existing infrastructure and storing hydrogen in the form of LOHCs, in contrast to compressed or liquefied H 2 In comparison, LOHC is less flammable and easier to handle.
[0023] It has been demonstrated that replacing hydrocarbons with heteroatoms (such as N, O, etc.) improves the reversible dehydrogenation / hydrogenation properties (Xie, Y., Milstein, D. ACS Appl. Energy Mater. 2019, 2(6), 4302-4308 https: / / doi.org / 10.1021 / acsaem.9b00523 ;Jorschick, H. et al. Sustainable Energy Fuels 2021,5(5),1311-1346 https: / / doi.org / 10.1039 / D0SE01369B ). The hydrogenation / dehydrogenation of N-ethylcarbazole (NEC) is mentioned here. In this case, N-ethylcarbazole (NEC) as a low-energy form is converted into a fully hydrogenated form (H12-NEC) as an energy-rich form according to the following reaction scheme (Scheme 2).
[0024]
[0025] Scheme 2: Special N-heterocyclic LOHC
[0026] H12-NEC is a liquid that can be stored at ambient temperature and ambient pressure. The storage density of hydrogen according to this reaction is about twice as high in terms of volume as in a 700 bar tank filled with hydrogen. Compared to a pressure vessel, the tank can take any form, which makes it easier to adapt to technical applications.
[0027] The dehydrogenation of LOHC is an endothermic process that operates at a feasible rate only at elevated temperatures. In any case, the endothermic nature of the dehydrogenation reaction has a negative impact on the overall efficiency of the LOHC system: releasing hydrogen from the LOHC requires a continuous supply of energy (heat) to the reactor to keep the reaction going. Therefore, thermal management in the LOHC system is critical in order to heat the LOHC reactor to produce enough hydrogen, which is provided for generating electricity in the fuel cell. There are several methods to this extent. The first method is to directly electrically heat the catalytic element, which includes a catalytically active layer on top of the heating element or conductor material (US2011265738A, US2011268651A). In some designs, the required electricity is extracted from the fuel cell (US2015056526A), or the electricity from the fuel cell is used to heat a heat transfer medium, which is connected to the LOHC reactor via a heat exchanger (CN108940150A). Another method is to install a burner to heat the LOHC reactor by directly burning H 2 Heat is generated by burning additives contained in the LOHC fluid (such as biofuels, fossil fuels, methanol, (bio)ethanol) (DE102014006430A1). Another method is to use a heat pump (CN112768724A).
[0028] As already explained, suitable catalysts are required for the hydrogenation and dehydrogenation processes in the LOHC cycle. These catalysts can be heterogeneous catalysts or homogeneous catalysts. The best known catalysts to date are heterogeneous catalysts containing metal particles on an oxidic support. The metals are usually selected from, but not limited to, the group of Ni, Co, Pd, Pt, Rh, Ru, Pd, Ir, Re. Examples of oxidic supports are alumina, titania, silica, ceria, etc. These catalysts can in principle be used for both the hydrogenation and dehydrogenation parts of the LOHC cycle, although Ni is mainly used for hydrogenation. Suitable catalysts can also be obtained using combinations of metals, alloys and catalyst support combinations.
[0029] Noble metal catalysts have a long chemical history in the hydrogenation or dehydrogenation of organic molecules. Heteroatom-doped noble metal catalysts have also been developed. For example, Pd(111)-P type catalysts have been proposed for cyclohexene dehydrogenation. Compared with pure Pd-catalysts, P-modification leads to an increase in the deactivation barrier, thereby reducing benzene decomposition, which improves catalyst stability and reduces rate (Sampath, A., & Fla-herty, DW (2020), Effects of phosphorus addition on selectivity and stability of Pd model catalysts during cyclohexenedehydrogenation. Catalysis Science & Technology, 10 (4), 993-1005). In addition, Ouma et al. studied Si, P, S and Se surface additives as catalytic activity boosters for dehydrogenation of methylcyclohexane to toluene-A liquid organic hydrogen carrier system: Densityfunctional theory insights;Materials Chemistry and Physics, 279, 125728).
[0030] In addition, SiO 2 PtP 2 The nanoparticles showed high selectivity but low activity in the hydrogenation of propylene and acetylene and in the dehydrogenation of propane. The P:Pt molar ratio varied between 10 and 50. The catalysts were obtained by impregnation of a solid support with Pt followed by calcination at 225 °C. The latter was treated with H 3 PO 4 Impregnation, followed by calcination at 600 °C and reduction with hydrogen at 550 °C, resulted in the formation of crystalline PtP 2 phase, which is confirmed by the characteristic X-ray diffraction pattern of the compound (JT Miller et al., Structuraland Catalytic Properties of Isolated Pt 2 +Sites in Platinum Phosphide(PtP 2 ); ACS Catalysis, 11(21), (2021), 13496-13509).
[0031] In addition to Pt, it is known that crystalline Ru 2 P-based catalysts are also used in hydrogenation and dehydrogenation reactions. For the hydrogenation of toluene to methylcyclohexene, the Ru catalyst supported on SiO 2 Crystalline Ru 2 P showed significantly higher activity for this reaction (Furukawa, S.; Matsu-nami, Y.; Hamada, I.; Hashimoto, Y.; Sato, Y.; Komatsu, T. Remarkable Enhancement in Hydrogenation Ability by Phosphidation of Ruthenium: Specific Surface Structure Having Unique Ru Ensembles. ACS Catal. 2018, 8(9), 8177-8181. https: / / doi.org / 10.1021 / acscatal.8b02582). In this case, Ru was determined by high-resolution transmission electron microscopy (HR-TEM). 2 The crystallinity of the P phase. In contrast, the same publication also states that the toluene hydrogenation activity of Pt, Pd, Ir, Rh phosphides is lower than that of the corresponding catalysts without phosphorus.
[0032] Similarly, as confirmed by HR-TEM, 2 Crystalline Ru 2 Ru is also a known catalyst for propane dehydrogenation (Ma, R.; Yang, T.; Gao, J.; Kou, J.; Chen, JZ; He, Y.; Miller, JT; Li, D. Composition Tuning of Ru-Based Phosphide for Enhanced Propane Selective Dehydrogenation. ACS Catal. 2020, 10.). Crystalline Ru supported on activated carbon 2P has also been shown to be a catalyst for the hydrogenation and dehydrogenation of N-heterocyclic compounds (Shao, F. Geometric and Electronic Effects on the Performance of a Bifunctional Ru2P Cat-alyst in the Hydrogenation and Acceptorless Dehydrogenation of N-Heteroarenes. Chinese Journal of Catalysis 2021, 10). It should be noted that the crystalline Ru 2 The presence of the P phase is crucial for their catalytic properties.
[0033] The low reactivity, the high reaction temperatures required and the pressure conditions imposed limit the applicability of carbon-containing molecules as hydrogen storage materials and are incompatible with the operating temperatures of, for example, conventional PEM fuel cells. Therefore, the aim remains to discover more and better catalysts that allow further reduction of the temperatures required for the hydrogenation / dehydrogenation processes of LOHC-based catalytic systems in order to make the overall process more energy-efficient and compatible with, for example, fuel cell implementations. Furthermore, the catalysts applied should be stable and durable in use, should be easy to prepare and should provide a less complex mode for the generation of electricity using LOHC in combination with fuel cells, in particular PEM, for hydrogenation and dehydrogenation.
[0034] These and other objects which are obvious to the person skilled in the art are achieved by providing a phosphorus-doped PGM-type catalyst and a catalytic system comprising said catalyst according to claims 1 and 7, respectively. The dependent claims of said claims relate to preferred aspects of the catalyst / catalytic system. Claims 8 to 12 relate to a process according to the invention for producing such a catalyst. Claims 13 to 17 relate to a catalytic system according to the invention. Claim 18 relates to a device for generating electric power and claim 19 protects the use of the catalytic system according to the invention.
[0035] These objects are achieved in a very facile yet still excellent manner by providing a phosphorus-doped platinum group metal (PGM)-type catalyst for the hydrogenation and dehydrogenation of organic hydrogen carrier molecules, especially liquid hydrogen carrier compounds, wherein the catalyst is supported on a solid carrier material, the phosphorus has an average formal oxidation state of ≤2 and is present in a PGM:P molar ratio x of 0.1 < x < 10, without containing a crystalline phosphide phase, and wherein the PGM is selected from the group consisting of Pt, Pd, Ru, Ir, Rh, and mixtures thereof. The oxidation state of phosphorus can be measured by known techniques such as X-ray photoelectron spectroscopy, chemical identification of the phosphorus phases present in the catalyst (Kim, S.S.; Britcher, L.; Kumar, S.; Griesser, H.J. XPS Study of Sulfur and Phosphorus Compounds with Different Oxidation States. JSM 2018, 47(8), 1913 - 1922. https: / / doi.org / 10.17576 / jsm-2018-4708-33). The PGM:P ratio can be determined by standard chemical analysis methods known to those skilled in the art, such as, for example, inductively coupled plasma optical emission spectrometry (ICP-OES). According to the present invention, by doping the supported PGM-type catalyst with a certain amount of phosphorus atoms, the rate of the hydrogenation reaction, especially the dehydrogenation reaction, of organic molecules such as perhydrobenzyltoluene (H12-BT) is surprisingly increased such that a given degree of dehydrogenation of higher than 50% can be achieved in a time period that is at least 20% shorter. According to the known prior art, this would hardly be obvious.
[0036] In the present invention, the PGM catalyst is doped with a certain amount of phosphorus. This results in an increase in catalytic activity and makes it a viable catalyst for the hydrogenation and dehydrogenation of organic hydrogen carrier molecules, especially liquid organic hydrogen carrier molecules. The average formal oxidation state of phosphorus in such a composition is less than that in phosphate (PO 4 3- ) or phosphite (PO 3 3- ), indicating that when phosphorus is added in the form of phosphate or phosphite under reducing conditions, it is partially reduced. It is believed that this reduction will most likely not be to an average formal oxidation state of -3, since it is known that the PH 3 - species present at the time, bound to the solid PGM surface, is unstable at the elevated temperatures involved. Thus, preferably, the average formal oxidation state of the phosphorus atoms present is between -3 and 2, most preferably between -2 and 2, and extremely preferably between 0 and 2.
[0037] It is believed that the phosphorus dopant can act on the PGM-type catalyst by occupying certain positions on the outer sphere of the PGM-containing particles, which are usually located on the surface of the high surface area solid support material, which is well known in the field of heterogeneous catalysis. It can be expected that the phosphorus dopant on the surface of the PGM-containing particles affects the catalytic activity, and according to the present invention, the result is towards higher activity. Another possibility is that the phosphorus dopant is directly located on the surface of the high surface area, which can hinder the sintering of the PGM particles and thus contribute to the catalyst stability of the phosphorus-doped catalyst.
[0038] The platinum group metal (PGM) type catalysts used within the concept of the present invention are typical catalysts well known in various applications of heterogeneous catalysis, such as automotive exhaust treatment catalysts, emission control catalysts for stationary sources, and hydrogenation, dehydrogenation and oxidation reactions in large-scale chemical processes. Typically, the platinum group metal in question is deposited on a solid support material, such as but not limited to alumina, titania, ceria, silica, zirconium oxide and combinations thereof, by methods known to those skilled in the art (Heterogeneous Catalysis and Solid Catalysts, Ullmann En-cyclopedia 2009, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, p. 47 et seq.).
[0039] Solid support material is the material where the active PGM metal particles are located. These can be powders, powders processed into catalyst products (see the following paragraphs) or preformed or preformed solid bodies ("articles"). Solid support materials in powder form are all those that can be used in this case (for example in Heterogeneous Catalysis and Solid Catalysts, Ullmann Encyclopedia 2009, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, page 36 and subsequent pages). Generally, these are high surface area metal oxides, which have stability to a certain extent to the higher temperatures that may occur in the envisioned reaction. Other types such as carbon, carbides, nitrides, phosphates can also be solid support materials in powder form. The size of the powder particles is generally in the range of 0.1 μm to 500 μm, preferably 1 μm to 100 μm (ISO 13320-1-latest version of the application date). Specifically, the support material has a diameter of 30 μm. 2 / g to 250m 2 / g, preferably 100m 2 / g to 200m 2 / g of BET surface area (measured according to the latest version of German standard DIN 66132-application date). In this regard, preferred materials are, for example, aluminum oxide, aluminum oxide / silicon dioxide mixed oxide, magnesium oxide / aluminum oxide mixed oxide, ceria and ceria / zirconia mixed oxide, ceria / aluminum oxide mixed oxide, cordierite, corundum, aluminum titanate, cordierite-alumina, silicon nitride, zircon mullite, carbon, spodumene, aluminum oxide-silicon dioxide magnesium oxide, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, silicalite, aluminum oxide, aluminosilicate, silicoaluminophosphate, etc. Most preferably, those selected from the group consisting of aluminum oxide, silicon dioxide, magnesium oxide, titanium dioxide, zirconium oxide, ceria, a mixture comprising at least two of these materials, and a mixed oxide comprising at least two of these materials. Specifically, the mixed oxide is a solid solution. The solid support material is most preferably selected from the group consisting of alumina, zirconia, titania, ceria, SiC, AlTi, cordierite or mixtures or composites thereof. In the case of using alumina, it is preferably stabilized, for example, with 1 to 6 wt. %, in particular about 4 wt. %, of lanthanum oxide, silicon dioxide or barium oxide.
[0040] These powders can be processed into catalyst products of different forms, such as pellets, rings, extrudates such as flow-through or wall-flow monoliths, spheres, hollow spheres, particles. The size of these products usually varies between about 1 mm and 5 cm. Such catalyst products may contain pores (Synthesis of Solid Catalysts; de Jong, KP (editor); Wiley-VCH: Weinheim, 2009, Chapter 9). The powder support material can be treated before adding the PGM component. In this case, the selected one or more platinum group metals are deposited on such preformed solid support materials by methods known to those skilled in the art (Heterogeneous Catalysis and Solid Catalysts, Ullmann En-cyclopedia 2009, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, pages 47 and subsequent pages; Synthesis of Solid Catalysts; de Jong, KP (editor); Wiley-VCH: Weinheim, 2009, Chapters 3-8). In the second procedure, after the selected platinum group metal is deposited by methods known to those skilled in the art, the powder is processed into a catalyst product (Synthesis of Solid Catalysts; de Jong, KP (editor); Wiley-VCH: Weinheim, 2009, Chapters 3-9). The solid support material containing PGM in powder form can also be processed into catalytic products with a size range of 1 cm to 500 cm, such as ceramic foams, 3D printed forms, porous ceramic filters (HB Friedrich et al., Monoliths: A Review of the Basics, Preparation Methods and Their Relevance to Oxidation, Catalysts (2017), 7, 62). In a third procedure, the procedures mentioned here are combined so that a solid support material in powder form containing a platinum group metal is processed to give a catalytic product and subsequently a second portion of the same or different platinum group metal is deposited by methods known to those skilled in the art (Synthesis of Solid Catalysts; de Jong, KP (ed.); Wiley-VCH: Weinheim, 2009, Chapters 3-9).
[0041] In another embodiment, a solid support material containing PGM in powder form is processed into a catalytic article by applying it to the accessible surface of a preformed article, such as a flow-through monolith, a wall-flow filter or a corrugated monolith, a plate, a mesh, a wire, other preformed bodies, glass wool, metal wool (Avila et al., Chem. Eng. J. (2005), 109, 11-36) by, for example, washcoating, deposition or any other method intended to fix the solid support material to the outer surface of a solid body. The preformed article can in principle be any solid material, such as a metal, an oxidic material, a ceramic material, glass fiber, a polymer. Such articles are generally based on fiber materials or powder materials, which are preformed into a solid body by using appropriate adhesives, coatings, glues (HB Friedrich et al., Monoliths: A Review of the Basics, Preparation Methods and Their Relevance to Oxidation, Catalysts (2017), 7, 62).
[0042] PGM can also be directly loaded on the article as solid carrier material, such as the above-mentioned solid preformed article, form and main body. In the typical method of producing such articles, these articles are contacted with a solution of, for example, a platinum group metal according to methods known to those skilled in the art (Heterogeneous Ca-talysis and Solid Catalysts, Ullmann Encyclopedia 2009, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, page 47 and subsequent pages; Synthesis of Solid Cat-alysts; de Jong, KP (editor); Wiley-VCH: Weinheim, 2009, chapters 3-8). By this method, PGM is deposited on the article in the form of small clusters. They are then usually fixed to the outer surface of the article or the porous structure of the article by drying and calcining procedures.
[0043] PGMs suitable for the present invention have been previously identified. In a preferred aspect, the PGM is Pt and / or Pd. In a very preferred manner, Pt is the only PGM used within the scope of the present invention.
[0044] The flow-through monolith has thin, parallel gas flow channels extending from the inlet face to the outlet face of the substrate, such that the channels are open to fluid flow. These channels are substantially straight paths from their fluid inlet to their fluid outlet, defined by walls. The catalytic material may be applied as a patch coating so that the gas flowing through the channels comes into contact with the catalytic material. The flow channels of the monolith substrate are thin-walled channels that may have any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. Such structures may contain about 20-900 or more gas inlet openings (i.e., pores) per square inch of cross-section (3-140 pores / cm 2 ). The wall thickness, i.e. the thickness of the walls separating the channels of the substrate from one another, is typically about 0.005 cm to about 0.3 cm. The porosity of the flow-through monolith is greater than 20%, typically 20% to 70%, in particular 35% to 65% [measured in accordance with DIN 66133 - latest edition at the date of application]. The average pore size is at least 1 μm, for example 1.5 μm to 25 μm, preferably greater than 3 μm, in particular 5 μm to 18 μm [measured in accordance with DIN 66134 - latest edition at the date of application].
[0045] The wall-flow filter consists of a plurality of parallel channels formed by porous walls. The channels are alternately sealed at one of the two ends of the filter, so that a channel A is formed, which is open at the first side of the filter and sealed at the second side of the filter, and a channel B is formed, which is sealed at the first side of the filter and open at the second side of the filter. For example, a fluid flowing into channel A can only leave the filter via channel B and must flow through the porous wall between channel A and channel B for this purpose. The porosity of the finished substrate is greater than 40%, typically 40% to 75%, in particular 45% to 70% [measured according to DIN 66133-latest version at the date of application]. The average pore size is at least 7 μm, for example 7 μm to 34 μm, preferably greater than 10 μm, in particular 10 μm to 20 μm [measured according to DIN 66134-latest version at the date of application].
[0046] The corrugated monolith consists of alternating layers of flat sheets and corrugated sheets with regular curved folds or grooves. (See Figure 2). Channels are formed in the corrugated layers of the article by winding or stacking the combined flat sheets and corrugated sheets into the desired form. In principle, this structure can be made of any material that can form, combine and maintain such a structure, such as metal, ceramic, paper, polymer, glass fiber sheet. In order to stabilize the structure, one or more additional processing steps may be required, such as fusion welding, welding, gluing, coating, heating. Such corrugated substrates and their manufacture are disclosed in WO2010066345A1, and its teachings can be applied to the present invention without departing from the scope of the claims. Corrugated catalytic articles are obtained by applying catalytically active materials on the surface of the channels or in the porous structure of these materials.
[0047] A preferred embodiment of the corrugated catalytic article is a corrugated article based on a glass fiber substrate. The glass fiber substrate has a wall density of at least 50 g / l but not more than 150 g / l and a porosity of at least 50%. The substrate monolith consists of a sheet of high silica content or a sheet of E-glass fiber. The high silica content glass sheet may optionally contain a metal oxide layer such as alumina, silica, TiO 2 Or diatomaceous earth, to stabilize the structure. In the present invention, the phosphorus-doped PGM catalyst according to the present invention loaded on a powder carrier is applied to the surface of the corrugated sheet and the flat sheet of the product. In another embodiment, the phosphorus-doped PGM catalyst according to the present invention loaded on a powder carrier is applied to the porous structure of the glass fiber material constituting the corrugated sheet and the flat sheet of the product. In another embodiment, the unloaded PGM metal and phosphorus are directly applied to the corrugated sheet and the flat sheet. In a typical method for producing such glass fiber products, these products are contacted with a solution of, for example, a platinum group metal according to methods known to those skilled in the art (Heterogeneous Cataly-sis and Solid Catalysts, Ullmann Encyclopedia 2009, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, pages 47 and subsequent pages); Synthesis of Solid Catalysts; de Jong, KP (editor); Wiley-VCH: Weinheim, 2009, chapters 3-8). By this method, the PGM is deposited on the article in the form of small clusters. The PGM clusters can be fixed to the outer surface of the glass fiber wall or inside the porous structure of the glass fiber wall by appropriate drying and calcination procedures known to those skilled in the art.
[0048] The amount of PGM for loading onto the solid support material or article can be selected by those skilled in the art. The selected amount should be as little as possible while providing sufficient catalytic activity, because excessive PGM makes the catalyst too expensive. Typically, the amount of PGM per weight of solid support material is in the range of 0.01 wt % to 8.0 wt %, preferably 0.1 wt % to 6.0 wt %, and most preferably 0.3 wt % to 5.0 wt %.
[0049] The PGM deposited on the solid support material is usually present in the form of small clusters in the nanometer range. In heterogeneous catalysis, the activity of the catalyst is determined by the total surface area of these small clusters, so that the larger the surface area, the higher the activity. Because small clusters provide a larger surface area and therefore provide a higher catalytic activity, small clusters are generally preferred in the catalyst. However, there is a lower limit to the diameter of the PGM clusters. For particles with a diameter lower than 1nm to 1.5nm, depending on the metal used, quantum effects have occurred, which may lead to a reduction in the expected catalytic activity. Those skilled in the art know the diameter range of the most effective deposited PGM clusters for the present invention. For example, a PGM-type catalyst comprises a PGM cluster having a size y of 1.0nm≤y≤50nm on a solid support material. The particle size is determined by the CO adsorption capacity of the catalyst, which is measured by CO pulse chemisorption under appropriate conditions on the catalyst, as is known to those skilled in the art (Tanabe, T.; Nagai, Y.; Hira-bayashi, T.; Takagi, N.; Dohmae, K.; Takahashi, N.; Matsumoto, S.; Shinjoh, H.; Kondo, JN; Schouten, JC; Brongersma, HH Low Temperature CO Pulse Ad-sorption for the Determination of Pt Particle Size in a Pt / Cerium-Based Oxide Cat-alyst. Applied Catalysis A: General 2009, 370(1-2), 108-113. https: / / doi.org / 10.1016 / j.apcata.2009.09.030). Preferably, the diameter y of the deposited PGM-type catalyst is 1.5 nm≤y≤20 nm, most preferably 2.0≤y≤10 nm, most preferably 2.0≤y≤5.0 nm.
[0050] To produce a phosphorus-doped catalyst, the PGM clusters fixed to a solid support material are then contacted with a phosphorus substance and maintained under reducing conditions at ≥450° C., for example for at least 1 hour, to form a phosphorus-doped PGM-type catalyst. The phosphorus compound is used in an amount such that the above-mentioned PGM:P molar ratio x is 0.1≤x≤10, preferably 0.3≤x≤5, more preferably 0.4≤x≤2 and most preferably 0.5≤x≤1. It should be explicitly emphasized that the phosphorus-doped PGM-type catalyst does not contain a phosphide phase, such as XP 2 In particular, X-ray diffraction of the catalysts of the present invention does not show crystalline PtP 2 Typical characteristics of the phase (see Figure 1 ), indicating that there is no PtP 2 .
[0051] In addition, the phosphorus-doped PGM-type catalyst may contain additional promoter or inhibitor atoms. These are known to those skilled in the art. They may promote the reduction or oxidation of the organic hydrogen carrier molecule in question or inhibit undesirable side reactions, such as decomposition of the organic hydrogen carrier. Therefore, in a preferred aspect, the phosphorus-doped PGM-type catalyst comprises an additional dopant selected from the group consisting of S, Se, Si, and most preferably S.
[0052] The phosphorus-doped PGM-type catalyst of the present invention can be obtained by a first process, wherein:
[0053] i) loading at least one PGM on a solid support material;
[0054] ii) contacting it with a salt or acid of an oxide of phosphorus; and
[0055] iii) It is subsequently treated with a reducing agent at a temperature of ≥ 450°C.
[0056] Steps i) and ii) can be carried out sequentially, i.e. i) first and ii) later. However, steps i) and ii) of the process of the invention can also be carried out simultaneously by contacting the support material with a solution containing a PGM precursor and a salt or acid of an oxide of phosphorus. Subsequently, the obtained material is treated with a reducing agent at a temperature of ≥ 450°C.
[0057] As already indicated, it is readily known to those skilled in the art from the art of producing catalysts for automobile exhaust gas treatment applications how to deposit at least one PGM on the surface of a solid support. Deposition can advantageously be carried out, for example, by incipient wetness techniques, wet impregnation, nanoparticle deposition or precipitation from a PGM solution (Chattopadhyay, S. Review on Monolithic Ceramic Catalysts in Different Applications Support Materials, Incorporation Techniques and Physical Properties, Topical Reviews (2005), Vol. 65 (4), p. 179 et seq.). In a preferred manner, deposition of the PGM onto the surface area of the solid support material is carried out by incipient wetness impregnation (https: / / en.wikipedia.org / w / index.php?title=Incipient_wetness_impregnation&oldid=946130465) or precipitation techniques such as sedimentation precipitation (http: / / www.fhi-ber-lin.mpg.de / acnew / department / pages / teaching / pages / teaching__wintersemes-ter__2006_2007 / koehler_preparation_supported_catalysts_111006.pdf).
[0058] In a typical procedure for deposition precipitation, for example, an aqueous solution of PGM is contacted with a solid support material. By appropriately changing the pH, the PGM becomes insoluble and deposited on the surface of the solid support material and inside the pores of the solid support material. Then, the material is dried and calcined to fix the PGM to the solid support material. The drying and calcining can be performed by those skilled in the art. The specific calcination temperature depends on the PGM metal, the specific compound in the precursor solution, and the deposition conditions. Typically, calcination is performed at 200°C to 600°C, more preferably at 250°C to 500°C, and most preferably at about 300°C to 450°C. Typically, the gas atmosphere in the calcination step is ordinary air, but changes can also be applied. Such changes include the absence or change of the partial pressure of oxygen and water, and the addition of one or more auxiliary gases such as hydrogen, carbon monoxide, ammonia, NO, methanol, ethanol or other small organic molecules such as (C 1 -C 3 )alkanes and / or (C 1 -C 3 )Olefins.
[0059] The PGM solution that can be used in this case is known to those skilled in the art (Preuster, P., Papp, C., & Wasserscheid, P. (2017). Liquid organic hydrogen carriers (LOHCs): toward a hydrogen-free hydrogen economy. Accounts of chemical re-search, 50 (1), 74-85.). In a preferred embodiment, palladium and / or rhodium and / or platinum are used to form the PGM-type catalyst of the present invention. Examples of palladium include palladium; halides, such as palladium chloride; inorganic salts, such as nitrates and sulfates of palladium; carboxylates, such as acetates of palladium; and hydroxides, halides of palladium; inorganic salts, carboxylates and hydroxides of tetraamminepalladium and hexaamminepalladium; alkoxides, dinitrodiamminepalladium, and oxides. Preferred examples include nitrates and nitrates of dinitrodiamminepalladium, tetraaminepalladium, and hexaaminepalladium; carboxylates; and hydroxides, and more preferred examples include nitrates (palladium nitrate) and nitrates of tetraaminepalladium and hexaaminepalladium; carboxylates; and hydroxides.
[0060] Examples in the case of using platinum include platinum; halides such as platinum bromide and platinum chloride; inorganic salts such as hexahydrogenate, chloroplatinic acid (H2[PtCl6]) and tetranitrogenate of platinum; carboxylates such as platinum acetate; and hydroxides and halides of platinum; inorganic salts, carboxylates and hydroxides of tetraaminepalladium and hexaaminepalladium; alkoxides; dinitrodiammineplatinum, and oxides. Preferred examples include chloroplatinic acid (H2[PtCl6]) and dinitrodiammineplatinum, nitrates, carboxylates, hydroxides and hexahydrogenate of tetraamineplatinum and hexaamineplatinum, and more preferred examples include chloroplatinic acid (H2[PtCl6]) and dinitrodiammineplatinum, nitrates, carboxylates, hydroxides and hexahydrogenate of tetraamineplatinum and hexaamineplatinum.
[0061] Examples in the case of using rhodium include rhodium; halides such as rhodium chloride; inorganic salts such as nitrates, sulfates, hexaammine salts and hexacyano salts of rhodium; carboxylates such as acetates of rhodium; and hydroxides, alkoxides, and oxides of rhodium. Preferred examples include nitrates and hexaammine salts, and more preferred examples include nitrates, especially rhodium nitrate. The above-mentioned compounds of platinum group metals in the present invention (PGM sources or precursors) can be used alone or as a mixture of two or more compounds. In the case of mixing PGM sources or precursors, it is preferred to use the same kind of counter ions.
[0062] The PGM-containing material is prepared by contacting the support material with one or more PGM-containing solutions. The support material has been discussed above. After one or more PGM particles are deposited on the solid support material by, for example, impregnation, incipient wetness impregnation, nanoparticle deposition, etc., the material is dried and optionally calcined, as described above.
[0063] In the next step, phosphorus doping has to be performed. In one embodiment of the invention, phosphorus doping is performed by contacting the PGM-containing material with a salt or acid of a phosphorus oxide known to those skilled in the art. Preferred compounds in this regard are ammonium salts, alkali metal salts, alkaline earth metal salts or other metal salts of phosphorus oxides, such as phosphates, phosphites or hypophosphites and their acids. Even more preferred are acids or salts derived from acids of phosphorus oxides, selected from phosphoric acid, phosphonic acid (H 3 PO 3 ), hypophosphorous acid, diphosphoric acid. Most preferred in this regard are phosphonic acid and hypophosphorous acid and their respective salts. These precursors are preferably contacted with the PGM-type catalyst in the form of a solution. The concentration of the solution should reach the desired PGM:P ratio (see above). Typically, the concentration of the precursor is in the range of 0.01 mmol / L to 1000 mmol / L, more preferably 0.5 mmol / L to 100 mmol / L and most preferably 1 mmol / L to 10 mmol / L.
[0064] After contacting with the above compounds, the mixture obtained is optionally dried and calcined again in order to fix the phosphorus compound on the PGM-type catalyst. The skilled person knows what temperature is required. The calcination is preferably carried out at 100° C. to 800° C., more preferably 200° C. to 500° C. and most preferably 300° C. to 450° C., under an oxidizing, reducing or inert gas flow.
[0065] Now, in a final step, the phosphorus precursor present on the PGM-type catalyst is treated with a reducing agent in order to reduce the formal oxidation state of phosphorus to ≤ 2, as described above. This reduction can be carried out according to the methods of a person skilled in the art (Kou, J. et al., (2021). Structural and Catalytic Properties of Iso-lated Pt 2+ -Sites in PlatinumPhosphide(PtP 2), ACS Catalysis, 11 (21), 13496-13509; Alvarado Rupflin, L. et al., Platinum group metal phosphides as heterogeneous catalysts for the gas-phase hydroformylation of small olefins, ACS Catalysis, (2017), 7 (5), 3584-3590; Alvarado Rupflin, L. et al., Platinum group metal phosphides as efficient catalysts in hydroprocessing and syngas-related catalysis, Cata-lysts, (2018) 8 (3), 122). Preferably, this can be carried out with a reducing agent which is molecular hydrogen or a compound that produces hydrogen when reacting with a proton. These compounds are known to those skilled in the art (Beghi, GE, Review of thermochemical hydrogen production, International Journal of Hydrogen Energy, (1981), 6 (6), 555-566; https: / / en.wikipe-dia.org / wiki / Hydrogen#Discovery_and_use). In a preferred manner, the reduction is carried out under an atmosphere of hydrogen or a mixture of hydrogen and an inert gas such as argon or nitrogen.
[0066] The reduction temperature depends on the type of metal and reducing agent used and is known to those skilled in the art. The reduction is carried out at a suitable temperature, which depends on the reducing agent, usually above 300° C. Preferably, when hydrogen is used, the reduction is carried out at a temperature of ≥450° C. More preferably, the reduction is carried out at a temperature of ≥500° C., and most preferably, the reduction temperature is set to ≥550° C. The upper limit of the temperature does not appear to be critical, but for reasons of efficiency it should not reach above 700° C., preferably not exceeding 650° C.
[0067] In an exemplary production method, a suitable precursor (e.g., H 2 [PtCl 6 ]、Pt(NH 3 ) 4 (NO 3 ) 2 etc.) with an oxidative support (e.g. Al 2O 3 ) to synthesize the PGM-type catalyst. 2 O) and calcined (e.g., 400° C., 2 hours, air), with, for example, H 3 PO 3 After the second impregnation (e.g., stirring at room temperature for 16 hours) and the removal of the solvent (H 2 O), the catalyst is heated at 600°C with, for example, N 2 10% H 2 The reduction was 2 hours.
[0068] In an alternative method, the phosphorus-doped PGM-type catalyst of the present invention can also be obtained by the following method, wherein:
[0069] i) loading at least one PGM on a solid support material;
[0070] ii) making it and selected from PH 3 , alkylphosphine or arylphosphine; and iii) optionally contacting it with a reducing agent. Contacting the PGM on the solid support material with the phosphorus compound as described above will result in the simultaneous phosphation and reduction of the PGM. The reduced phosphorus-containing compound can also be obtained in situ by decomposing a suitable precursor compound (Sheng, Q.; Li, X.; Prins, R.; Liu, C.; Hao, Q.; Chen, S. Understanding the
[0071] Reduction of Transition-Metal Phosphates to Transition-Metal
[0072] Phosphides by Combining Temperature-Programmed Reduction and
[0073] Infrared Spectroscopy.Angewandte Chemie International Edition 2021,
[0074] 60(20),11180-11183. https: / / doi.org / 10.1002 / anie.202100767 ;Liu, D.;
[0075] Li, X.; Wei, L.; Zhang, T.; Wang, A.; Liu, C.; Prins, R.
[0076] Disproportionation of Hypophosphite and Phosphite.Dalton Trans.2017,46(19),6366-6378. https: / / doi.org / 10.1039 / C7DT00243B .).
[0077] In an alternative method of the invention, phosphorus doping is performed by contacting the PGM-containing material with a phosphorus-containing compound in a reduced oxidation state. Preferably, the phosphorus-containing compound is selected from an alkyl phosphine, an aryl phosphine or a phosphane (PH 3 ) of an organic or inorganic compound. It is also possible, for example, to decompose a corresponding phosphorus-containing precursor compound such as sodium hypophosphite (NaH 2 PO 2 ), in situ forming a phosphorus-containing compound in a reduced oxidation state. The PGM-containing material is contacted with the above-mentioned compound at a temperature of 100°C to 800°C, more preferably 200°C to 600°C, and most preferably 250°C to 450°C. When phosphane is used, additional treatment with a reducing agent is optionally carried out. Hydrogen can be used as a reducing agent, which has been mentioned in the first production method. In a preferred manner, the reaction is carried out in an atmosphere of hydrogen or a mixture of hydrogen and an inert gas such as argon or nitrogen. The reaction is carried out at a high temperature of ≥100°C. More preferably, the reduction is carried out at a temperature of 200°C to 600°C, and most preferably, the reduction temperature is set between 250°C and 450°C. The conditions adopted and the materials used in the first method are also applicable to this alternative method after necessary changes.
[0078] In an exemplary production method, a suitable precursor (e.g., H 2 [PtCl 6 ], Pt(NH 3 ) 4 (NO 3 ) 2 The PGM-type catalyst is synthesized by impregnating an oxidized support (e.g., Al2O3) with, for example, Pt. After impregnation (e.g., stirring at room temperature for 16 hours), removal of the solvent (H 2 O) and calcination (e.g. 400°C, 2 hours, air), followed by a subsequent phosphating-reduction step. The PGM-containing material is placed in a tube furnace, for example, with PH 3 contact, wherein sodium hypophosphite is present in a ceramic boat upstream of the PGM-containing material. The furnace is then heated to N 2 The phosphorus-containing precursor is heated to 300°C for 2 hours to decompose and form PH 3 , which is believed to result in phosphating and reducing the PGM-containing catalyst. No further reduction step is required in this case.
[0079] In another embodiment, the present invention relates to a catalytic system for the hydrogenation and dehydrogenation of organic hydrogen carrier molecules, in particular liquid hydrogen carrier compounds, comprising:
[0080] i) the phosphorus-doped PGM-type catalyst of the present invention;
[0081] ii) an organic hydrogen carrier molecule; and
[0082] iii) optional solvent.
[0083] Organic hydrogen carrier molecules can store and release hydrogen as needed in the presence of a suitable catalyst. Such molecules are known to those skilled in the art. Organic hydrogen carrier molecules suitable for the intended purpose are those with sufficient hydrogenation / dehydrogenation efficiency. Preferably, the organic hydrogen carrier molecule in question should have a minimum hydrogen storage and release capacity of at least 3 wt %, more preferably at least 4 wt % and most preferably at least 5 wt % under the test conditions. The wt % refers only to hydrogen and molecules.
[0084] In a preferred aspect, the organic hydrogen carrier molecule is advantageously selected from liquid organic hydrogen carriers containing hydrocarbon aromatic compounds, liquid organic hydrogen carriers containing heteroaromatic compounds, and ketones, esters, carboxylic acids, CO 2 As far as liquid organic hydrogen carriers are concerned, the person skilled in the art knows which LOHC compounds are most effective for the intended purpose, namely to establish a catalytic system which allows, under technically reasonable conditions, preferably reversible hydrogenation and dehydrogenation of LOHCs.
[0085] LOHCs that can be used in the catalytic system of the present invention are disclosed in the prior art. Preferably, as already mentioned, the LOHCs used for the purposes of the present invention should be able to reversibly hydrogenate and dehydrogenate within a suitable temperature and pressure range, in particular under conditions (operating conditions) that can be established in a vehicle comprising a fuel cell. In another preferred aspect, the liquid organic hydrogen carrier is selected from the group consisting of saturated or unsaturated cyclic hydrocarbons optionally containing N atoms and / or O atoms.
[0086] For example, in a more preferred aspect, the LOHC used in the catalytic system of the present invention comprises a hydrocarbon aromatic compound. Liquid organic hydrogen carriers also refer to partially or fully dehydrogenated forms. Partially hydrogenated compounds may still have reasonable H 2capacity. Therefore, when referring to hydrocarbon compounds as LOHCs in the present context, possible reaction products of the hydrogenation of low-energy (dehydrogenated) forms of said compounds are also included, since they are essentially the same in the present context. For example, in the case of aromatic hydrocarbons, a partially hydrogenated form of such a compound is no longer chemically an "aromatic" compound. However, since it is a partial hydrogenation product of an aromatic compound, it is still considered an aromatic LOHC. The phrase "hydrocarbon aromatic compound" then refers to a compound obtainable by hydrogenation of an aromatic compound. In this regard, even more preferred compounds are those mentioned in the prior art section. Extremely preferred are those selected from the group consisting of toluene, benzyltoluene, diarylmethylene (such as dibenzyltoluene).
[0087] In a further preferred aspect, the liquid organic hydrogen carrier comprises a heteroaromatic compound. Partially hydrogenated heteroaromatic compounds may still have a reasonable H 2 capacity. This is essentially the same in the present context, but the compound is no longer chemically an "aromatic" compound. Therefore, when speaking of a heteroaromatic compound as a LOHC in the present context, possible reaction products of the hydrogenation of the heteroaromatic compound are also included. The phrase "heteroaromatic compound" identifies the fact that it is obtainable by hydrogenation of a heteroaromatic system consisting of a hydrocarbon and at least one heteroatom (e.g. N, O, S).
[0088] In a further preferred aspect, the compounds for hydrogen storage in organic molecules which allow reversible dehydrogenation and hydrogenation in the catalytic system of the present invention are ketones, esters, carboxylic acids, CO 2 Particularly preferred is C 3 -C 10 Ketones (such as acetone, butanone or acetophenone), C 1 -C 10 Esters (e.g., formates, acetates or propionates, wherein the ester substituent is an organic group, such as an alkyl or aryl group, such as methyl, ethyl, propyl, benzyl, phenyl or naphthyl), C 1 -C 10 Carboxylic acids (such as formic acid, acetic acid or benzoic acid). The most preferred are LOHC systems, such as dibenzyltoluene (DBT) / H18-DBT, toluene / methylcyclohexane, pyridine / piperidine, N-ethylcarbazole (NEC) / H12-NEC, CO 2 / Methanol, CO 2 / formic acid, acetone / isopropanol. According to the present invention, the most preferred LOHC compound is selected from the group consisting of acetone / isopropanol, perhydrobenzyltoluene / benzyltoluene, perhydrodibenzyltoluene / dibenzyltoluene, N-ethylcarbazole (NEC) / H12-NEC.
[0089] In this regard, compounds which can theoretically be hydrogenated and dehydrogenated in the catalytic system of the invention but which would provide too many side reactions during these cycles or which are unmanageable in the catalytic system for other reasons (such as low flowability) are not covered by the definition of LOHC according to the invention. In particular, thermal or chemical instability (side reactions or decomposition under working conditions), for example by reaction with H 2 O, O 2 According to the present invention, it is envisaged that in reversible hydrogenation and dehydrogenation, favorable organic hydrogen carrier molecules can be operated under the test conditions for 5000 cycles, but compared with the fresh catalytic system under the same conditions, the H 2 The storage / release capacity is maintained at at least 50%, more preferably at least 70% and most preferably at least 90%.
[0090] Preferably, for example aldehydes are excluded from the definition of LOHC compounds according to the invention, in particular aldehydes which may react readily with themselves and are therefore not available for reversible hydrogenation / dehydrogenation reactions as required for the purposes of the present invention.
[0091] The solvents that may be optionally present in the catalytic system are those that dissolve the LOHC to the necessary extent and remain liquid under the working conditions. For example, it is conceivable that, due to the low reaction temperature, some OHC molecules will become solid or at least waxy and are therefore not suitable for use as hydrogen carrier molecules. In order to still react in a liquid state, it may become important to add a solvent, which is used to keep the OHC molecules in a liquid state. All solvents known to those skilled in the art that dissolve the corresponding OHC to the necessary extent and are inert under the applied reaction conditions can in principle be used here. Available solvents are selected from the group consisting of linear, branched or cyclic alkanes, such as pentane, hexane, heptane or octane. Aromatic molecules such as benzene or toluene are also feasible. In addition, ketones such as acetone and MIBK can be used. In this regard, alcohols, ethers, esters, halogenated alkanes DMSO or DMF can also be considered.
[0092] In this sense, the components of the catalytic system are mixed together in the respective compartments, heated to the preferred temperature and thus dehydrogenated. As compartments, the same as for H 2 The consumption or storage device has a fluid-connected airtight tank, beaker, container, etc. Although a certain hydrogen pressure may exist, it is preferably not necessary to apply excess H2 pressure for dehydrogenation. The temperature of the reaction is advantageously varied between -40°C and 350°C, more preferably between 100°C and 320°C and most preferably between 180°C and 280°C. Hydrogenation at a certain H 2The hydrogenation is carried out under a pressure of 0.01 bar to 200 bar, more preferably 0.1 bar to 100 bar and most preferably 10 bar to 50 bar. The temperature of the hydrogenation varies between -40°C and 300°C, more preferably 100°C to 300°C and most preferably 150°C to 250°C. The temperature and hydrogen pressure conditions mentioned above are referred to as working conditions according to the present invention.
[0093] As already indicated, the catalytic system is a heterogeneous mixture comprising the components of the catalytic system. The system envisaged should be compatible with the conditions necessary for the intended purpose, i.e. to establish a catalytic system that allows the organic hydrogen carrier to undergo reversible hydrogenation and dehydrogenation reactions under technically reasonable conditions, such as operating conditions, in particular under conditions present in a fuel cell-driven vehicle.
[0094] In another embodiment, the present invention relates to a device for generating electricity, the device comprising a fuel cell and a catalytic system of the present invention. Such a device for generating electricity preferably also includes a reactor containing the catalytic system of the present invention and a system preferably for heating the reactor, and optionally a system for separating hydrogen from an organic hydrogen carrier, and optionally one or more heat exchangers. In one aspect, the system for heating the reactor includes a burner for burning hydrogen. (Niermann, M. et al., Energy Environ. Sci. 2019, 12 (1), 290-307; https: / / doi.org / 10.1039 / C8EE02700E In another aspect, the system for heating the reactor includes one or more electrical heating bodies (such as plates or meshes) connected to an external power source (such as a battery or a generator). In another aspect, the electrical heating bodies are connected to a fuel cell, and the fuel cell provides power to the heating system.
[0095] The preferred aspects of the catalytic system according to the invention apply mutatis mutandis to this device. In a very preferred mode, the catalytic system of the invention functions in a one-pot compartment, wherein the hydrogenation and dehydrogenation reaction steps are carried out in an alternating manner by varying the reaction conditions such as the hydrogen partial pressure or the temperature (e.g. EP 3 221 256 B1).
[0096] In a third embodiment of the invention, the use of the catalytic system of the invention is also claimed. The catalytic system of the invention is used to provide hydrogen to a fuel cell for the generation of electricity. Preferably, the hydrogen is supplied in a purified form, for example as required for PEM fuel cell applications. The preferred aspects of the catalytic system and the device also apply mutatis mutandis to the use of the invention.
[0097] The LOHC catalytic system for releasing hydrogen from the fuel advantageously includes, for example, (1) a tank containing a hydrogen-rich LOHC liquid, (2) a second tank containing a dehydrogenated LOHC liquid, (3) a dehydrogenation reactor, (4) facilities for heating the reactor, such as a hydrogen burner, an oil heater, an electric heater, etc., (5) facilities for purifying the hydrogen product gas, which typically includes a cooler or heat exchanger to cool the product, and (6) a gas-oil separation unit. The purified hydrogen gas is then fed to a fuel cell to generate electricity (Niermann, M. et al. Energy Environ. Sci. 2019, 12(1), 290-307; https: / / doi.org / 10.1039 / C8EE02700E ; Preuster, P. et al., J. Hydrog. Ener. 2018, 43(3), 1758-1768).
[0098] The present invention relates to the storage and release of hydrogen in organic liquids. A complete cycle using, for example, LOHC consists of the following: (1) hydrogenation in the form of dehydrogenation of the LOHC system using hydrogen gas and (2) dehydrogenation of the hydrogenated form of the LOHC in a catalytic system. Thus, the hydrogen is stored in the hydrogenated form of the LOHC. The hydrogenated form of the LOHC has a higher energy density per volume than compressed or liquefied hydrogen, is easier to transport or store, and is safer to handle due to the lower flammability of the organic liquid. The catalytic system of the present invention enables those skilled in the art to carry out the envisaged release and storage of hydrogen at much lower temperatures, thereby providing a technically applicable solution for mobile vehicles equipped with fuel cells for generating electricity. This is not obvious in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0099] Figure 1 .Al 2 O 3 Support, 3.1 wt% Pt / Al 2 O 3 X-ray diffraction patterns of the P-doped Pt-P-catalyst (reduced at 600 °C) and the P-doped Pt-P-catalyst (all reduced at 600 °C). XRD was measured between 10° and 90° with a step size of 0.0170 and a step time of 100 s. The diffraction pattern of the P-doped Pt catalyst shows γ-Al overlapped with Pt 2 O 3 characteristics, while PtP 2 The typical characteristics of Al cannot be observed. Reference data for the following substances are included: 2 O 3(Gutierrez,G.;Taga,A.;Johansson,B.Theoretical structure determination of gamma-(Al2O3);Physical Review,Serie3.B-Con-densed Matter(18,1978-),2002,65,012101 / 1-012101 / 4),Pt(Bredig,G;Al-lolio,R;Roentgenuntersuchungen an katalytisch wirkenden Metallen, Zeitschriftfuer Physikalische Chemie (Frankfurt Am Main, 1927, 126, 41-71) and PtP 2 (Wyckoff, RWG, The second edition of Structure of Crystals, The Chemical Catalog Company Inc., New York 1931, pp. 234 and 238).
[0100] Figures 2a to 2c; Top: Corrugated fiberglass showing alternating flat and corrugated layers. Bottom left: Catalytic article obtained by winding together a flat sheet and a corrugated sheet. In this example, the corrugated structure consists of metal. Bottom right: Catalytic article obtained by stacking a flat sheet and a corrugated sheet of fiberglass paper.
[0101] Figure 3 : Intermittent apparatus for the dehydrogenation of perhydrobenzyltoluene. It consists of a three-necked round-bottomed 100 mL flask (1) equipped with a magnetic stirrer, a heating jacket (2), a magnetic stirring plate (3), a double-necked attachment (4) for supplying Ar during the heating / inerting phase and for storing the catalyst (5). One neck of the flask is used for the thermocouple and for sampling via a septum (6). The released hydrogen is directed through a reflux condenser (7) and a diffuser (8) and then to the exhaust. Example
[0102] Material
[0103] Al 2 O 3 The carrier material was provided by Umicore NV / SA (150m 2 / g BET surface area, 13.7nm pore size, 0.490g / cm 3Total pore volume) or provided by Sasol (Puralox, 136m 2 / g BET surface area, 13.7nm pore size, 0.466g / cm 3 total pore volume).
[0104] Chloroplatinic acid hexahydrate (H 2 [PtCl 6 ]6H 2 O, 38%-40% Pt) was purchased from abcr GmbH.
[0105] Sodium hypophosphite monohydrate (NaH 2 PO 2 ·H 2 O), phosphoric acid (H 3 PO 3 ) and GC grade acetone (Suprasolv) were purchased from Merck KGaA.
[0106] Example 1
[0107] This example shows that an active catalyst for LOHC dehydrogenation is obtained by the process according to the invention.
[0108] In the first step, Pt / Al 2 O 3 Catalyst A was prepared by adding Al 2 O 3 The carrier and the corresponding amount of H 2 [PtCl 6 ] aqueous solution (pH = 4) to obtain 3 wt% Pt / Al 2 O 3 The catalyst was stirred at room temperature overnight (300 rpm, 16 h). The solvent was then removed in a rotary evaporator (80 ° C, 100 mbar), and the dried catalyst was then calcined in a muffle furnace at 400 ° C for 2 hours under air flow (heating rate 10 ° C / min). A portion of the catalyst was then heated to 10% H 2 / N 2 The reduction was carried out at 440 °C for 2 hours to obtain 3.0 wt% Pt / Al 2 O 3 (Catalyst A - reduced).
[0109] In a second impregnation step, another portion A is impregnated with phosphonic acid (H 3 PO 3 ) to form catalyst B. Here, Pt / Al 2 O 3 , then add the corresponding amount of P-precursor H 3 PO3 , resulting in a loading of 0.9 wt %. The mixture was stirred at room temperature overnight (300 rpm, 16 h). The solvent was then removed in a rotary evaporator (80 ° C, 100 mbar), and the dried catalyst was then heated to 10% H 2 / N 2 The catalyst contained 2.9 wt% Pt and 0.8 wt% P, corresponding to a Pt:P molar ratio of 0.58.
[0110] To test the performance of the catalyst powder in the dehydrogenation of perhydrobenzyltoluene (H12-BT), a glass batch apparatus ( Figure 3 ). In this experiment, 15.00 g of H12-BT and 250 mg of catalyst were placed in the apparatus so that the H12-BT:Pt molar ratio was 2000:1. The reaction temperature was adjusted to 250°C. A liquid sample (about 0.5 mL) was taken after 360 minutes of reaction time, and the degree of dehydrogenation (DoDh) of the liquid phase was measured by refractive index. From the DoDh, the hydrogen productivity can be calculated.
[0111] Table 1 :
[0112] <![CDATA[H production within 360 minutes 2 production]]> Initial production rate (5 minutes) Catalyst A-Reduction <![CDATA[69gH 2 / gPt]]> <![CDATA[0.73gH 2 / (gPt min)]]> Catalyst B <![CDATA[85gH 2 / gPt]]> <![CDATA[0.85gH 2 / (gPt min)]]>
[0113] For catalyst A-reduction, the total production of hydrogen was 69 g after 6 hours. H2 / g Pt For catalyst B, the total hydrogen production after 6 hours was 85 g. H2 / g Pt , which corresponds to a 23% increase in the total hydrogen production in the P-doped catalyst (Catalyst B).
[0114] Example 2
[0115] This example shows that compared with unphosphated Pt / Al 2 O 3 In contrast, the use of Pt-P prepared by the phosphating method of the present invention reduces the formation of methylfluorene, which is an indicator of LOHC degradation.
[0116] Catalyst A-Reduction was prepared as described in Example 1.
[0117] By mixing 1 g of unreduced Pt / Al 2 O 3 Catalyst C was prepared by placing the catalyst A (catalyst A from Example 1) in a ceramic boat in a tube furnace. Upstream of this, 250 mg of NaH 2 PO 2 ·H 2O was placed in another ceramic boat. Then the furnace was heated to pure N 2 The mixture was heated to 300°C at a rate of 10°C / min and maintained at this temperature for 2 hours. 2 PO 2 Decompose into Na 2 HPO 4 and PH 3 , whereby the latter should reduce Pt / Al 2 O 3 The catalyst was simultaneously modified with phosphorus. The catalyst contained 2.5 wt. % Pt and 0.4 wt. % P, corresponding to a Pt:P ratio of 1.0.
[0118] The performance of the catalyst powder in the dehydrogenation of perhydrobenzyltoluene (H12-BT) was tested as described in Example 1. The liquid phase was analyzed using gas chromatography (GC-FID) and the methylfluorene content was determined.
[0119] Table 2 :
[0120]
[0121]
[0122] For Catalyst A-reduction, the total methylfluorene content in the liquid phase after 6 hours was 0.43%, and for Catalyst C, the total methylfluorene content in the liquid phase after 6 hours was 0.36%, corresponding to a 16% reduction in methylfluorene formed with the P-doped catalyst (Catalyst C).
[0123] Example 3
[0124] This example shows the effect of reduction temperature on the Pt-P / Al prepared by the method of the present invention. 2 O 3 Effect of catalysts on the dehydrogenation performance of H12-BT.
[0125] A portion of Catalyst A (prepared as described in Example 1) was stirred in 10% H 2 / N 2 The reduction was carried out at 440 °C for 2 hours to obtain 3.0 wt% Pt / Al 2 O 3 (Catalyst A-440), and another portion was reduced in 10% H2 / N2 at 600°C for 2 hours to obtain 3.1 wt% Pt / Al2O (Catalyst A-600).
[0126] A catalyst was prepared as described in Example 1 (Catalyst B) containing 2.7 wt% Pt and 0.6 wt% P (Catalyst B-600). Another catalyst was prepared as described in Example 1 (Catalyst B), but reduced at 440°C instead of 600°C to obtain a catalyst with 3.0 wt% Pt and 0.6 wt% P (Catalyst B-440), corresponding to a Pt:P molar ratio of 0.8.
[0127] The performance of the catalyst powder in the dehydrogenation of perhydrobenzyltoluene (H12-BT) was tested as described in Example 1.
[0128] Table 3 :
[0129] <![CDATA[H output within 360 minutes 2 output]]> Initial production rate (after 5 minutes) Catalyst A-440 <![CDATA[56g H2 / g Pt ]]> <![CDATA[0.22g H2 / (g Pt my)]]> Catalyst A-600 <![CDATA[33g H2 / g Pt ]]> <![CDATA[0.17g H2 / (g Pt my)]]> Catalyst B-440 <![CDATA[19g H2 / g Pt ]]> <![CDATA[0.03g H2 / (g Pt my)]]> Catalyst B-600 <![CDATA[81g H2 / g Pt ]]> <![CDATA[0.51g H2 / (g Pt my)]]>
[0130] The total production of hydrogen after 6 hours was 56 g for catalyst A-440 and catalyst A-600, respectively. H2 / g Pt and 33g H2 / g Pt For catalyst B-440 and catalyst B-600, the total production of hydrogen after 6 hours was 19 g, respectively. H2 / g Pt and 81g H2 / g Pt This corresponds to an increase in the total hydrogen production of 45% (relative to A-440) and 145% (relative to A-600) in the P-doped catalyst (B-600) reduced at 600°C. On the other hand, the P-doped catalyst (B-440) reduced at 440°C showed a 66% lower hydrogen productivity than catalyst A-440.
[0131] Example 4
[0132] This example shows the effect of Pt:P ratio on Pt-P / Al 2 O 3 Effect of catalyst performance on H12-BT dehydrogenation.
[0133] Catalysts with different P-loadings were prepared as described in Example 1 (Catalyst B) by adjusting the precursor ratios to achieve final Pt:P ratios of 1.75 (Catalyst B-1.75), 0.99 (Catalyst B-0.99), 0.58 (Catalyst B-0.58) and 0.40 (Catalyst B-0.40), respectively.
[0134] The performance of the catalyst powder in the dehydrogenation of perhydrobenzyltoluene (H12-BT) was tested as described in Example 1.
[0135] Table 4 :
[0136] <![CDATA[H within 360 minutes 2 Output]]> Initial production rate (5 minutes) Catalyst B-1.75 <![CDATA[24g H2 / g Pt ]]> <![CDATA[0.15gH 2 / (gPt min)]]> Catalyst B-0.99 <![CDATA[67g H2 / g Pt ]]> 0.49gH2 / (gPt min) Catalyst B-0.58 <![CDATA[85g H2 / g Pt ]]> 0.85gH2 / (gPt min) Catalyst B-0.40 <![CDATA[56g H2 / g Pt ]]> 0.42gH2 / (gPt min)
[0137] Compared with other phosphorus-modified catalysts with lower and higher P-contents, catalyst B-0.58 achieved the highest hydrogen production within 360 min reaction time.
[0138] Example 5
[0139] This example shows that the activity of the phosphorus-modified Pt-catalyst prepared by the process of the present invention is increased compared to the unphosphorized Pt-catalyst in the hydrogenation of benzyltoluene (HO-BT) to perhydrobenzyltoluene (H12-BT).
[0140] Catalyst AH (Catalyst A-reduced, 3 wt% Pt) was prepared as described in Example 1, and Catalyst BH (Catalyst B, 3 wt% Pt, 0.6 wt% P) was prepared as described in Example 1.
[0141] In order to test the performance of the catalytic powder in the hydrogenation of benzyltoluene (HO-BT) to perhydrobenzyltoluene, an autoclave was filled with 0.8 mol of HO-BT and a catalyst amount corresponding to a Pt concentration of 0.04 mol%. The temperature was raised to 210°C and a hydrogen pressure of 30 bar was applied. In order to follow the progress of the reaction, liquid samples were taken from the autoclave reactor during the reaction and the degree of hydrogenation (DoH) of the liquid phase was measured by gas chromatography. As a measure of activity, the time required to reach 99% DoH was compared.
[0142] Table 5 :
[0143]
[0144]
[0145] The time required to reach 99% DoH was 30 minutes for Catalyst AH and 7.5 minutes for Catalyst BH. This corresponds to a 3-fold increase in the hydrogenation reaction rate when using the P-doped catalyst (Catalyst BH).
Claims
1. A phosphorus-doped PGM-type catalyst for the hydrogenation and dehydrogenation of organic hydrogen carrier molecules, in particular liquid hydrogen carrier compounds, wherein the catalyst is supported on a solid support material, the phosphorus has an average formal oxidation state of ≤2 and is present in a PGM:P molar ratio x of 0.1≤x≤10, while not comprising a crystalline phosphide phase, and wherein the PGM is selected from the group consisting of Pt, Pd, Ru, Ir, Rh and mixtures thereof.
2. The phosphorus-doped PGM-type catalyst according to claim 1, Features The solid support material is selected from the group consisting of alumina, zirconia, titania, ceria, SiC, AlTi, cordierite or a mixture or composite thereof.
3. The phosphorus-doped PGM-type catalyst according to claim 1 or 2, Features The PGM is Pt and / or Pd.
4. The phosphorus-doped PGM-type catalyst according to claim 1, Features The amount of PGM per solid support material is in the range of 0.01 wt% to 8 wt%.
5. Phosphorus-doped PGM-type catalyst according to one of the preceding claims, Features The PGM-type catalyst comprises the PGM having a size y of 1.0 nm≤y≤50 nm on the support.
6. Phosphorus-doped PGM-type catalyst according to one of the preceding claims, Features The PGM:P molar ratio x is 0.3≤x≤5.
7. Phosphorus-doped PGM-type catalyst according to one of the preceding claims, Features The catalyst comprises an additional dopant selected from the group consisting of S, Se, Si.
8. Process for producing a phosphorus-doped PGM-type catalyst according to one of claims 1 to 7, comprising the following steps: i) loading at least one PGM on a solid support material; ii) contacting it with a salt or acid of an oxide of phosphorus; and iii) It is subsequently treated with a reducing agent at a temperature of ≥ 300°C.
9. The method according to claim 8, Features The acid or salt of said acid derived from an oxide of phosphorus is selected from the group consisting of phosphoric acid, phosphonic acid, hypophosphorous acid, diphosphoric acid.
10. The method according to claim 8 or 9, Features The reducing agent is molecular hydrogen or a compound that generates hydrogen upon reaction with protons.
11. The method according to one of claims 8 to 10, Features The reduction temperature is set to be ≥550°C.
12. Process for producing a phosphorus-doped PGM-type catalyst according to one of claims 1 to 7, comprising the following steps: i) loading at least one PGM on a solid support material; ii) contacting it with a compound selected from the group consisting of PH3, alkyl phosphine or aryl phosphine; and iii) optionally contacting it with a reducing agent.
13. A catalytic system for the hydrogenation and dehydrogenation of organic hydrogen carrier molecules, in particular liquid hydrogen carrier compounds, the catalytic system comprising: i) a phosphorus-doped PGM-type catalyst according to one of claims 1 to 7; ii) an organic hydrogen carrier molecule; and iii) optional solvent.
14. The catalytic system according to claim 13, Features The organic hydrogen carrier is selected from the group consisting of saturated or unsaturated cyclic hydrocarbons optionally containing N atoms and / or O atoms.
15. The catalytic system according to claim 13 or 14, Features The organic hydrogen carrier molecule is a liquid organic hydrogen carrier comprising a hydrocarbon aromatic compound.
16. The catalytic system according to claim 13 or 14, Features The organic hydrogen carrier molecule is a liquid organic hydrogen carrier comprising a heteroaromatic compound.
17. The catalytic system according to claim 13 or 14, Features The organic hydrogen carrier includes a compound selected from the group consisting of ketones, esters, carboxylic acids, and CO2.
18. Device for generating electric power, comprising a fuel cell and a catalytic system according to one of claims 13 to 17.
19. Use of a catalytic system according to one of claims 13 to 17 for providing hydrogen to a fuel cell for the production of electricity.
Citation Information
Patent Citations
Self-heating dehydrogenation reaction system suitable for liquid hydrogen source material
CN108940150A
LOHC fuel cell power generation system and method
CN112768724A
Method for operating hydrogen gas station for e.g. passenger car, involves conveying partly hydrogenated liquid organic hydrogen carrier into chemical reactor, where hydrogen is not chemically bound as substance in carrier in gas station
DE102012004444A1
Method for supplying energy, in particular to off-grid or mobile consumers, device for carrying out such a method and mixture of substances usable therein
DE102014006430A1
gripping device for cannulas
DE102017201451A1